Analisis Sanitasi Lingkungan Rumah dengan Keberadaan Vektor Tikus di Kelurahan Sekar Jaya Kabupaten OKU - Mely Fitry; Yulis Marita (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Rats are mammals that are very detrimental and disrupt human life and welfare. Leptospirosis is one of the emerging infectious diseases caused by Leptospira bacteria. One of the factors that influence the existence of mice is environmental factors. In Sekar Jaya Village, the working area of ​​the Sekar Jaya Community Health Center, OKU Regency is a densely populated area, which can be seen in terms of house buildings and the position of residents' houses, most of which are close to each other. In several houses there were signs of mice. This research aims to determine the sanitation analysis of the home environment with the presence of rat vectors in Sekar Jaya Village, Sekar Jaya Health Center UPTD Working Area, Ogan Komering Ulu Regency in 2023. The research design is Cross Sectional. The population of all heads of families in Sekar Jaya Village is 2,373 heads of families with a sample size of 331 respondents. The statistical test used is the chi square test. Univariate analysis showed that 186 (56.2%) respondents had no rat vectors in their homes, 189 (57.1%) respondents with trash bin conditions met the requirements, 182 (55%) respondents with SPAL conditions met the requirements and As many as 173 (52.3%) respondents had no food waste. The results of the bivariate analysis revealed that the variables were trash can condition with a p value of 0.000, SPAL condition with a p value of 0.002, and food waste disposal with a p value of 0.000. There is a significant relationship between the condition of the trash can, the condition of the SPAL, and the disposal of food waste and the presence of rat vectors in Sekar Jaya Village.